2019
DOI: 10.36706/jp.v6i2.10171
|View full text |Cite
|
Sign up to set email alerts
|

Pendampingan Penulisan Proposal Penelitian Tindakan Kelas Dan Artikel Ilmiah Bagi Guru Di Sman 3 Palembang

Abstract: Classroom Action Research (CAR) is a study of teacher activities related to professional development in the class. The aims to improve the real and practical problems in improving the quality of classroom learning. Scientific articles are reports of research results presented and published in a recognized (accredited) scientific magazine (journal). The mentoring was conducted for four months at SMAN 3 Palembang. Beginning with a discussion of the learning issues facing the economics teacher then devising a pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
0
0
1
Order By: Relevance
“…The study results confirmed that classroom action research was essential to teachers' professional development because it could improve their competence in writing and recording (Koryati et al, 2019). In addition, to help solve the learning problems they face, teachers also get direct experience (from the planning stage to reporting).…”
Section: Resultssupporting
confidence: 62%
“…The study results confirmed that classroom action research was essential to teachers' professional development because it could improve their competence in writing and recording (Koryati et al, 2019). In addition, to help solve the learning problems they face, teachers also get direct experience (from the planning stage to reporting).…”
Section: Resultssupporting
confidence: 62%
“…Penelitian di sekolah berupa penelitian dalam siklus yang kecil, yaitu Penelitian Tindakan Kelas (PTK). Penelitian merupakan modifikasi dari penelitian tindakan (action research), yang dikembangkan dengan tujuan penyelesaian masalah sosial (Koryati, 2019).…”
Section: Pendahuluanunclassified